The Role of GST Gene Polymorphic Variants in Antipsychotic-Induced Metabolic Disorders in Schizophrenia: A Pilot Study - Irina A. Mednova; Ekaterina V. Mikhalitskaya; Natalia M. Vyalova; Diana Z. Paderina; Dmitry A. Petkun; Vladimir V. Tiguntsev; Elena G. Kornetova; Nikolay A. Bokhan; Svetlana A. Ivanova (Pharmaceuticals, 2025)
The life expectancy of patients with psychotic disorders is significantly shorter than that of the general population; antipsychotic-induced metabolic disorders play a significant role in reducing life expectancy. Both metabolic syndrome (MetS) and schizophrenia are multifactorial conditions. One area where the two conditions overlap is oxidative stress, which is present in both diseases. The glutathione-S-transferase (GST) system is a major line of defense against exogenous toxicants and oxidative damage to cells. The aim of our study was to perform an association analysis of gene polymorphisms with metabolic disorders in patients with schizophrenia treated with antipsychotic therapy. Methods: A total of 639 white patients with schizophrenia (ICD-10) from Siberia (Russia) were included in the study. Genotyping was carried out using real-time polymerase chain reaction for two single-nucleotide polymorphisms (SNPs) in the GSTP1 (rs614080 and rs1695) and one SNP in the GSTO1 (rs49252). Results: We found that rs1695*GG genotype of GSTP1 is a risk factor for the development of overweight (OR 2.36; 95% CI: 1.3–4.29; p = 0.0054). In the subgroup of patients receiving first-generation antipsychotics as basic therapy, the risk of overweight was associated with carriage of the rs1695*GG (OR 5.43; 95% CI: 2.24–13.16; p < 0.001) genotype of GSTP1 in a recessive model of inheritance. In contrast, an association of rs1695*G GSTP1 with obesity (OR: 0.42; 95% CI: 0.20–0.87; p = 0.018) was shown in the dominant model of inheritance in patients receiving second-generation antipsychotics. Conclusions: The pilot results obtained confirm the hypothesis of a violation of the antioxidant status, in particular the involvement of GSTP1, in the development of antipsychotic-induced metabolic disorders in schizophrenia. Further studies with larger samples and different ethnic groups are needed to confirm the obtained results.